Public-Private in The Modernization of The Health Reform - Mendoza, Pedro (1995)
We present a review of concepts around public an private in the process of modernization and heaIth sector reform currently ongoing in Perú. We begin with a general overview of the public and private concepts in differente functional levels of a generic health systems, namely, users function, provider function and financing function. We introduce then the concept of "public-private Mix" by using examples of international experience and also from national experiences. Finally, we propose some criteria for assessment of reform processes in health care systems when they inelude a purchaser-provider split, and we examine conditions to be taken in account if the introduction of market mechanisms and a higher private participation in health care provision is promoted, but preserving efficiency and quality of health care, and improving the equity principies of the system.